Hormonal Monitoring of Reproductive Status in Monogamous Wild Female Owl Monkeys (Aotus azarai) of the Argentinean Chaco - Fernandez Duque, Eduardo (2011)
The Neotropical owl monkeys (Aotus spp.) are a good model for evaluating the hypothesis that monogamy may arise if female reproductive cycles limit the mating potential of males. To evaluate this hypothesis, we first needed to assess the feasibility of using fecal sampling for monitoring the reproductive status of females. We collected fecal samples (n = 242, from 7 females) from wild adult Aotus azarai females in the Gran Chaco forests of Argentina during 3 years. Fecal estrone-1-glucuronide (E1C) and pregnenadiol-3-glucuronide (PdG) tended to rise in parallel during the luteal phase. The average cycle length was 22 ± 3 days (n = 5 females, 10 cycles). We identified 2 conceptive cycles and characterized the E1C and PdG profiles of 2 pregnancies. This report is the first of its kind on wild female owl monkeys. Despite the difficulties in sample collection and processing in the field and providing a species-specific validation in the laboratory, we show that fecal samples from A. azarai can be used for monitoring female reproductive status and function.